Expressing the Day of the Month in Biblical Hebrew: A Diachronic Perspective - Moshavi, Adina Mosak (Journal for semitics, 2021)
Biblical Hebrew (henceforth BH), like most languages, possesses two different kinds of numerals, cardinals, e.g., sheloshah (three) and ordinals, e.g., shelishi (third). While BH can generate a cardinal of any size, the ordinal paradigm in BH only goes up to ten, and there is no morphological or syntactic mechanism for combining ordinals to express higher numbers. BH compensates for its lack of higher ordinals by employing ordinal numerals in dedicated syntactic constructions. The present study is a diachronic corpus-based analysis of the syntax of one kind of cardinal phrase with ordinal meaning, the day-of-the-month expression. This study takes the syntactic and semantic accounts in Rothstein and Moshavi (2021) as its points of departure, and includes a construction not discussed in that publication. The study examines the synchronic and diachronic distributions of four constructions that account for nearly all occurrences of cardinal constructions with ordinal meaning: the appositional phrase (AP), the reduplicative construct phrase (RCP), the construct phrase (CP), and the bare numeral phrase (BN). The data presented reveals noteworthy developments in day-of-the-month expressions in Late Biblical Hebrew (LBH) that are also reflected in the extra-biblical Hebrew corpora of the Second Temple period. These results establish the syntactic expression of ordinality as a topic of significance for the broader endeavour of characterising the linguistic features of exilic and Second Temple Hebrew.